Indoor Air Photocatalytic Decontamination by UV–Vis Activated CuS/SnO2/WO3 Heterostructure - Enesca, Alexandru; Sisman, Viorel (Catalysts, 2022)
A titania-free heterostructure based on CuS/SnO2/WO3 was obtained by a three-step sol–gel method followed by spray deposition on the glass substrate. The samples exhibit crystalline structures and homogenous composition. The WO3 single-component sample morphology consists of fibers that serve as the substrate for SnO2 development. The CuS/SnO2/WO3 heterostructure is characterized by a dense granular morphology. Photocatalytic activity was evaluated under UV–Vis radiation and indicates that the WO3 single-component sample is able to remove 41.1% of acetaldehyde (64.9 ppm) and 52.5% of formaldehyde (81.4 ppm). However, the CuS/SnO2/WO3 exhibits a superior photocatalytic activity due to a larger light spectrum absorption and lower charge carrier recombination rate, allowing the removal of 69.2% of acetaldehyde and 78.5% of formaldehyde. The reusability tests indicate that the samples have a stable photocatalytic activity after three cycle (12 h/cycle) assessments. During light irradiation, the heterostructure acted as a Z-scheme mechanism using the redox ability of the CuS conduction band electrons and the SnO2/WO3 valence band holes to generate the oxidative species required for VOC removal.
Keywords: air decontamination; photocatalysis; semiconductors; acetaldehyde; formaldehyde